Genetic Population Structure of Yellowfin Tuna (Thunnus albacares) as Based Data of Fish Conservation in North Mallucas Sea - Nebuchadnezzar Akbar; Muhammad Aris (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
Tuna is a migratory species with high economic value. Utilization of tuna is increasing and growing every year. Fishing intensity of tuna in the Maluku Sea is high and can disrupt the population. The existence of the population will be threatened if not managed properly. The latest genetic information approach is necessary to prevent the population decline. The purpose of this research was to know the genetic structure of yellowfin tuna in North Maluku waters, Indonesi. Sampling was conducted in May-July 2016 in Morotai Island, Obi and Sanana, while secondary data was gathered in Ternate Island, Bacan and Ambon. A total of 72 samples were collected and analyzed. The result of the study found that the base length (bp) of the control region of mtDNA was found to be 512 bp (base pairs). the genetic distance in the nearest population is at Sanana and Obi (0.025). The results of genetic distance analysis between population found genetic similarity between Morotai-Sanana (0,021), Obi-Sanana (0,025), Obi-Morotai (0,026) and Ambon-Sanana (0,026), while the furthest genetic distance was found in Ternate-Bacan (0,040) and Ternate-Obi (0,042). The pairwise comparison test (Fst) shows a few genetic differentiation between yellowfin tuna populations. The value (Fst) of the yellowfin tuna population shows a strong gene flow between populations. The haplotype distribution shows a relationship between haplotypes in both yellowfin tuna, thus failing to show clade between different geographic locations. Unsustainable use can harm the population through genetic quality. Several approaches should be taken to support the life cycle of yellowfin tuna. The overall result shows that there has not been any change of genetic structure of yellowfin tuna in North Maluku Sea. Keywords : Haplotype, genetic distance, North Maluku, yellowfin tuna, pairwise comparison test